Vibration Cycling Did Not Affect Energy Demands Compared to Normal Cycling During Maximal Graded Test - Jemni, Monèm; Gu, Yaodong; Hu, Qiuli; Marina, Michel; Fessi, Mohamed Saifeddin; Moalla, Wassim; Mkaouer, Bessem; Konukman, Ferman (Frontiers in Physiology, 2019)
The aim of this study was to compare the physiological responses between a vibration induced cycling step protocol (Vib) and normal cycling (without vibration, no-Vib). Eighteen moderate trained males (age 24.1 ± 4.3 years; weight 76.5 ± 10.5 kg; height 178.0 ± 6.4 cm) have participated in this study. They randomly performed two gradual maximal exercise tests on two separate days using a new bike that automatically induces vibration cycling and the Corival cycle ergometer. The choice of two different bikes was made because of the impossibility to recreate the same power output without altering the cycling cadence on the vibration Bike. Both protocols were matched for power output and cycling cadence incrementations. Oxygen uptake (VO2), carbon dioxide production (VCO2), ventilation (VE), heart rate (HR), blood lactate and rating of perceived exertion (RPE) during each stage were continuously recorded. No statistical differences were founded for all variables when comparing the Vib to no-Vib trials, except a higher ventilation during the vibration trial at submaximal levels. The results of this study do not confirm those of previous studies stated that Vib increased metabolic demands during cycling exercise. Added vibration stimulus to an incremental cycling protocol does not affect physiological parameters.